High School Students' Ability to Design Physics Experiments through the ARBASC Model - Murdani, Eka; Sumarli, Sumarli; Sulistri, Emi; Rosdianto, Haris (STKIP Singkawang, 2025)
One of the problems in physics learning is the low level of students' ability to design experiments, especially on abstract concepts. Therefore, the purpose of this study was to determine the effectiveness of the application of the Augmented Reality-Based Argument of Society Commonsense (ARBASC) model on the ability to design physics experiments of high school students in West Kalimantan. This study is an applied research as a continuation of the development of the Augmented Reality-Based Argument of Society Commonsense (ARBASC) model. This model is applied to high school students in the West Kalimantan Province and is divided based on inland and coastal areas. Inland areas include Bengkayang Regency and Landak Regency while coastal areas include Sambas Regency and Singkawang City. The quantitative data analysis planned in this study for students' ability to design physics experiments by calculating the total average score and the average score of each element of the experimental design for each learning meeting. Data on students' ability to design physics experiments is obtained by looking at the trend of increasing average scores and scores for each element of the experimental design which are arranged in the form of Student Worksheets in designing experiments. Data collection on the ability to design experiments is carried out from one learning meeting to the next.